Beneficial effects of irisin in experimental paroxetine-induced hyperprolactinemia - Ercan, Zubeyde; Dogru, Meryem Sedef; Ertugrul, Nazife Ulker; Yardimci, Ahmet; Canpolat, Sinan (Springer, 2022)
Objective It is known that selective serotonin reuptake inhibitors (SSRIs), represent an important and effective treatment of depression and other psychological disorders, these medications can increase prolactin levels mainly through activation of the serotonergic pathway. In this study, we aimed to determine the beneficial effects of irisin on paroxetine, a SSRI, induced hyperprolectinemia and in some other reproductive hormonal changes associated with hyperprolactinemia. Methods Thirty two male Spraque-Dawley rats were used and divided into four groups including sham-operated control (vehicle), irisin (100 ng/kg/day for 28 days with mini-osmotic pumps), paroxetine (treated with 20 mg/kg paroxetine by oral gavage), irisin and paroxetine+irisin groups (n = 8). Serum prolactin (PRL), kisspeptin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone and 5-alpha reductase levels were determined with enzyme-linked immunosorbent analysis (ELISA). Results In animals treated with paroxetine, PRL level increased and testosterone level decreased significantly (p < 0.05). Serum LH level was significantly increased in the group, but no significant changes were observed in the FSH, kisspeptin and 5-alpha reductase levels. Serum prolactin levels was significantly decreased in the group treated with irisin. While no significant difference was observed in kisspeptin, FSH and 5-alpha reductase levels, an increase in serum LH and testosterone levels with irisin administration (p < 0.05). Conclusion In conclusion, chronic irisin exposure may reverse paroxetine-induced hyperprolactinemia. These results indicate that irisin may have the potential to be used as a therapeutic agent by primarily affecting paroxetine-induced increased prolactin and decreased testosterone levels.
Keywords: Prolactin; Irisin; Testosterone; Paroxetine